Relationship Between Dental and Oral Health Services in Dental Polyclinic to Patient Satisfaction in Community Health Centerpasar Gambir Kota Tebing Tinggi 2025 - Naro Ida Sari G. Manihuruk; Romauli Anna Teresia Marbun; Novita Br Ginting Munthe (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Patient visits to obtain dental and oral health services have decreased significantly in recent years in carrying out dental and oral examinations with Patient Satisfaction at the Pasar Gambir Health Center, Tebing Tinggi City. The purpose of this study was to describe and analyze the relationship between dental and oral health services and patient satisfaction at the Pasar Gambir Health Center, Tebing Tinggi City. This type of research is quantitative research using a cross-sectional design. Descriptive research is research directed at describing or describing a condition in a community or society. The population in this study were patients with patient satisfaction at the Pasar Gambir Health Center, Tebing Tinggi City in August-October 2024. The sample in this study was patients at the Pasar Gambir Health Center, Tebing Tinggi City, totaling 65 people. This study will be conducted from November 2024 to April 2025. The level of patient satisfaction is generally in the moderate to high category, but service improvements are still needed in terms of physical facilities and time management. There is a significant relationship between all dimensions of SERVQUAL (tangibles, reliability, responsiveness, assurance, and empathy) with the level of patient satisfaction. The conclusion is that there is a relationship between the level of patient satisfaction from the aspects of tangibles, reliability, responsiveness, assurance, and empathy towards dental and oral health services with patient satisfaction at the Pasar Gambir Health Center, Tebing Tinggi City.